ECM based injectable thermo-sensitive hydrogel on the recovery of injured cartilage induced by osteoarthritis. (5th November 2018) - Li, Yitong; Cao, Jie; Han, Shangcong; Liang, Yan; Zhang, Tingting; Zhao, Han; Wang, Libin; Sun, Yong
Abstract: Intra-articular injection of anti-inflammatory drugs can be a promising strategy for recovery of injured articular cartilage. We prepared a series of injectable thermo-sensitive composite hydrogels, composed of Pluronic F127, glycosaminoglycan (GAG) and bone morphogenetic protein (BMP-2), which was designed to mimic extracellular matrix (ECM). The rheological properties and dissolution rate of composite hydrogels containing chondroitin sulfate or with different hyaluronic acid molecular mass (10k, 90k, 800k) were investigated. Meanwhile, bovine serum albumin (BSA) or FITC-BSA was chosen as model drug loaded into PF/GAG hydrogels to study their sustained release behavior in vitro . The results showed that hydrogels could maintain shapes for more than 16 days and the release rate of BSA in PF/GAG composite gels was much slower than in PF127 gels, due to the affinity between BSA and GAG. Furthermore, increasing the molecular weight of hyaluronic acid correspondingly increased hydrogel dissolution rate and BSA release in the hydrogels. Subsequently, MTT experiments were performed to investigate the toxicity of the hydrogels on mouse pre-osteoblast cell MC3T3-E1. In vivo anti-inflammation results showed that PF/GAG@BMP-2 composite hydrogels had the most efficient efficacy on recovery of injured cartilage, which is induced by osteoarthritis, compared to the control groups (PF127@BMP-2 or BMP-2 saline solution).